2015
DOI: 10.1177/1203475415616073
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis and Smoking

Abstract: This literature review is in favor of a positive association between the prevalence of smoking and psoriasis as well as an association between smoking and severity of psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 42 publications
0
15
0
2
Order By: Relevance
“…A previously published meta-analysis determined that that smoking is an independent risk factor for the development of psoriasis and that patients with established psoriasis continue to smoke more than patients without psoriasis [9]. Another meta-analysis showed not only a positive association between the presence of psoriasis and the prevalence of smoking, but also between tobacco and the severity of psoriasis [10].…”
Section: Smokingmentioning
confidence: 99%
“…A previously published meta-analysis determined that that smoking is an independent risk factor for the development of psoriasis and that patients with established psoriasis continue to smoke more than patients without psoriasis [9]. Another meta-analysis showed not only a positive association between the presence of psoriasis and the prevalence of smoking, but also between tobacco and the severity of psoriasis [10].…”
Section: Smokingmentioning
confidence: 99%
“…Various studies have shown increased prevalence of cigarette smoking and alcohol consumption in patients with psoriasis [ 128 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 ]. A recent meta-analysis also demonstrated a significant association between smoking and psoriasis disease severity [ 158 ]. However, it is not clearly defined whether cigarette smoking and alcohol consumption may increase the risk of developing psoriasis, or whether they occur as a consequence of psoriasis-associated psychological stress.…”
Section: Psoriasis and Cardiovascular Risk Factorsmentioning
confidence: 99%
“…Studies have revealed a significant increase in Hcy levels in smokers compared with non-smokers [27–30]. Meanwhile, a systematic literature review and meta-analysis identified significant association between the prevalence of smoking and psoriasis [31].…”
Section: Possible Causes Of High Hcy Levels In Psoriasismentioning
confidence: 99%